2021
DOI: 10.1186/s12876-021-01880-9
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype associations of polymorphisms within the gene locus of NOD-like receptor pyrin domain containing 3 in Swiss inflammatory bowel disease patients

Abstract: Background Genetic variations within the regulatory region of the gene encoding NOD-like receptor pyrin domain containing 3 (NLRP3) have been associated with Crohn’s Disease (CD). NLRP3 is part of the NLRP3-inflammasome that mediates the maturation of IL-1β and IL-18. Carrying the major allele of the single nucleotide polymorphisms (SNPs) rs10733113, rs4353135 and rs55646866 is associated with an increased risk for CD. We here studied the impact of these polymorphisms on clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In contrast, there have been fewer studies examining the association between the NLRP3 rs10733113 polymorphism and disease. However, rs10733113 has been linked to elevated Crohn’s disease risk, and the rs10733113 G allele is reportedly associated with a reduction in the need for surgery and in maximal disease activity in patients with Crohn’s disease [ 17 ]. The rs10733113 G allele is also reportedly associated with an early-onset skin disease in psoriatic arthritis patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, there have been fewer studies examining the association between the NLRP3 rs10733113 polymorphism and disease. However, rs10733113 has been linked to elevated Crohn’s disease risk, and the rs10733113 G allele is reportedly associated with a reduction in the need for surgery and in maximal disease activity in patients with Crohn’s disease [ 17 ]. The rs10733113 G allele is also reportedly associated with an early-onset skin disease in psoriatic arthritis patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This SNP has been linked to many different diseases including diabetes, COVID-19, and bladder cancer [ 14 16 ]. The rs10733113 polymorphism in the NLRP3 gene has also been studied in the context of inflammatory bowel disease [ 17 ] and psoriatic arthritis [ 18 ], although its relationship with cancer remains to be studied at length. The association between the NLRP3 rs10754558 and rs10733113 polymorphisms and CC risk remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“… 44 The NLRP3 inflammasome plays a significant role in the pathogenesis of colitis, although NLRP3 was found to have both protective and disadvantageous functions in studies on mucosal immunity. Different results are associated, for example, with the mouse/human genetic backgrounds, 62 according to the composition of the gut microbiota, 63 with different colitis models, 64 or according to the method of inducing colitis (the concentration of DSS, the continuance of DSS delivery, and the number of cycles).…”
Section: Nod-like Receptors Regulate Homeostatic Intestinal Epithelia...mentioning
confidence: 99%
“…Studies indicate that some genotypes of the NLRP3 inflammasome may be associated with the affectability of patients with IBD and could represent biomarkers for the evaluation of IBD severity. A Swiss cohort study found that three NLRP3-related single nucleotide polymorphisms (RS10733113, RS55646866, rs4353135) were negatively related to CD ( 145 ). Moreover, some negative results were found ( 146 ).…”
Section: The Role Of Nlrp3 Inflammasome In the Pathomechanism Of Dige...mentioning
confidence: 99%